Indoor and Outdoor Volatile Organic Compounds at Office Buildings in Kuwait - Humood F. Al-Mudhaf; Abdel-Sattar I. Abu-Shady; Nabeel M. Al-Khulaifi (Air, Soil and Water Research, 2013)
A total of 800 indoor (I) and outdoor (O) air samples from eight large office buildings (LOBs) were analyzed for 78 VOCs using the latest sampling and preconcentration technology. Of these VOCs, 73 and 66 were detected in the I and O samples, respectively, at various levels and proportions. The I/O ratios were > 1, and ethanol exhibited the highest ratio of 14.7. The levels of aliphatic hydrocarbons were higher in LOBs located in the southern region of Kuwait, where the majority of industrial activities are located. By contrast, these levels were significantly lower in LOBs located in the northern and far northern regions, where industrial activities are absent. There was evidence of CFCs leaking from HVAC systems in several of the LOBs. BTEX inter-species ratios suggest that vehicular emissions contributed less to the outdoor air composition at the LOB at Jahra compared to other LOBs. Alcohols and carbonyls were the first and second most abundant classes of chemicals, respectively, in the VOC mixtures at the LOBs. None of the VOCs exceeded the recommended air quality limits.